2002
DOI: 10.1093/embo-reports/kvf053
|View full text |Cite
|
Sign up to set email alerts
|

Histone acetylation: a switch between repressive and permissive chromatin

Abstract: The organization of eukaryotic chromatin has a major impact on all nuclear processes involving DNA substrates. Gene expression is affected by the positioning of individual nucleosomes relative to regulatory sequence elements, by the folding of the nucleosomal fiber into higher-order structures and by the compartmentalization of functional domains within the nucleus. Because site-specific acetylation of nucleosomal histones influences all three aspects of chromatin organization, it is central to the switch betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
642
1
5

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 838 publications
(660 citation statements)
references
References 77 publications
12
642
1
5
Order By: Relevance
“…While histone acetylation events contribute to gene activation, the patterns of acetylation are diverse and distinct depending on the regulatory loci [57]. A comprehensive mapping of 18 histone acetylation marks in CD4 + T cells revealed that H3K9ac, H3K18ac, and H3K27ac are mainly located in regions surrounding the transcription start sites (TSS), whereas H4K8ac is elevated in promoter and transcribed regions of active genes [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…While histone acetylation events contribute to gene activation, the patterns of acetylation are diverse and distinct depending on the regulatory loci [57]. A comprehensive mapping of 18 histone acetylation marks in CD4 + T cells revealed that H3K9ac, H3K18ac, and H3K27ac are mainly located in regions surrounding the transcription start sites (TSS), whereas H4K8ac is elevated in promoter and transcribed regions of active genes [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…MLL catalyzes di-(H3K4me2) and trimethylation of lysine 4 of histone H3 (H3K4me3) (Hess, 2004). These histone modifications as well as acetylation of histone H3 (H3K9K14ac) and H4K16ac are associated with transcriptionally active regions (Eberharter and Becker, 2002;Santos-Rosa et al, 2002;Dion et al, 2005). Conversely, trimethylation of lysine 9 of histone H3 (H3K9me3) and trimethylation of lysine 27 of histone H3 (H3K27me3) are repressive marks.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely accepted that this densely packed DNA structure is maintained by the enzymatic activity of the histone deacetylases (HDAC), which maintain the histones in a deacetylated state. Deacetylated histones prevent the binding of transcription factors and suppress the transcriptional machinery [1][2][3]. Inhibition of HDACs results in hyper-acetylation and unravelling of DNA permitting gene activation.…”
Section: Introductionmentioning
confidence: 99%